Medical Communication Systems Utilizing Optical Nanoantenna and Microstrip Technology - Badr, Munaf Fathi; Murdas, Ibrahim A.; Aldhahab, Ahmed (Iraqi Journal for Electrical and Electronic Engineering, 2024)
Many technical approaches were implemented in the antenna manufacturing process to maintain the desired miniaturiza- tion of the size of the antenna model which can be employed in various applied systems such as medical communication systems. Furthermore, over the past several years, nanotechnology science has rapidly grown in a wide variety of applications, which has given rise to novel ideas in the design of antennas based on nanoscale merits, leading to the use of antennae as an essential linkage between the human body and the different apparatus of the medical communication system. Some medical applications dealt with different antenna configurations, such as microstrip patch antenna or optical nanoantenna in conjugate with sensing elements, controlling units, and monitoring instruments to maintain a specified healthcare system. This study summarizes and presents a brief review of the recent applications of antennas in different medical communication systems involving highlights, and drawbacks with explores recommended issues related to using antennas in medical treatment.